Feasibility Analysis for The Development of Integrated Coconut Industry in Tidore Islands, North Maluku - Angela Wulansari; Hamidin Rasulu; Suryati Tjokrodiningrat; Nahu Daud; Johan Fahri; Suwito Suwito; Muhammad Asril Arilaha; Nurhasanah Nurhasanah; Husen Alting (International Journal on Food, Agriculture and Natural Resources, 2023)
Coconut is the number one commodity in North Maluku. Nevertheless, mostly the coconut farmer is lived in poverty. Therefore The Government of Tidore Islands planned to build an integrated coconut industry in its administration area. This research aimed to analyze the feasibility of integrated coconut industry and to decide the main coconut product of the industry. The analysis consisted of market aspect, raw material availability, technology aspect, financial aspect, applied technic, and the impact on society and environment. The market analysis result showed there were 4 food products and 2 non-food products that were suitable to develop in Tidore Islands. Further analysis, which was financial aspect showed white copra was suitable to be the main product of The Integrated Coconut Industry in Tidore Islands. The production of white copra needed IDR 2.795.000.000 as initial capital investment. It was predicted to make a profit IDR 1.766.520.000 /year, the NPV value was IDR 3.702.044.248,88, the IRR value was 64,899% and the PBP was 2,5 years. Coconut husk and coconut shell will be processed to be coconut fiber and charcoal. Based on the result analysis of all the aspects, Integrated Coconut Industry in Tidore Islands is feasible to be established.